PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 5 TANJUNG PUNAK - Buniam, Buniam; Kurniaman, Otang; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low learning result of IPS class V SDN 5 Tanjung Punak on IPS subjects. Can be seen from the Minimum Criteria of Completeness (KKM) established by the school that is 70, from 21 students of class V that reach KKM is 7 students (33.33%) and who do not reach KKM is 14 students (66.67%) with average class 60.28. The purpose of this study is to improve the learning outcomes of IPS students class V SDN 5 Tanjung Punak with the application of cooperative learning model type numbered heads together. This study presents the learning results obtained from Daily Deuteronomic values before the action with an average of 60.28 increased to 77.48 in cycle I, and increased again to 80.95 in cycle II. Teacher activity in first cycle of first meeting was 58% with sufficient criteria, second meeting with value 71% with good criterion. In the first cycle of the first meeting, teacher activity was 79% with good criteria, and at the second meeting was 87% with very good criteria. Student activity on first cycle of first meeting is 63% with good criterion, second meeting is 67% with good criterion. In the first cycle of the first meeting, the student activity was 79% with good category, and at the second meeting was 83% with very good criteria. Based on the results of this study, it can be proved that the application of cooperative learning model numbered heads together can improve the learning outcomes of IPS students of grade 5 SDN 5 Tanjung Punak.Keywords: numbered heads together, IPS learning result